Subjectivity and the Social World : a Collection of Essays around Issues Relating to the Subject, the Body and Others. - Feldges, Tom (Cambridge Scholars Publishing, 2014)
At a time when the US government is spending enormous amounts of money on a project called BRAIN and the European Union has committed itself to the multi-million Human Brain Project, the chances of revealing the workings of the neuronal components of the brain are as good as they have ever been. Nevertheless, even if brain functions - or the entire brain - could be simulated on a computer one day, as the EU project aims for, the question of the relation between the experiencing subject and th ...